1993
DOI: 10.1590/s0101-81751993000300003
|View full text |Cite
|
Sign up to set email alerts
|

Ecologia de pequenos mamíferos silvestres da Mata Atlântica, Brasil: I. ciclos reprodutivos de Akodon cursor, Nectomys squamipes e Oryzomys nigripes (Rodentia, Cricetinae)

Abstract: ABSTRACT. ECOLOGY OF SMALL MAMMALS FROM OE ATLANTIC FOREST, BRASIL. I. REPROOUTIVE CYCLE OF AKODON CURSOR, NECTOMYS SQUAMIPES ANO ORYZOMYS NIGRIPES (ROOENTIA, CRICETINAE). ln this work are determined lhe productive periods and the number of fixed embl)'os/pregnancy in the species of non-nying small mammals in four different stages of regeneration of the Atlantic Forest in Silva Jardim and Casimiro de Abreu (Rio de Janeiro). Akodon cursor, Nectornys squarnipes and Oryzornys nigripes showed repeated oestrus in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
12

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 9 publications
0
3
0
12
Order By: Relevance
“…Fonseca and Kierulff (1989) and Pereira et al (1993) observed the same reproductive pattern, which could be related not only to food but also to habitat availability. The habitat of this rodent in the study area was reduced due to the flooding of marshes and streams, and due to the scarcity of litter and midstore during the rainy periods (Gentile and Fernandez, 1999).…”
Section: Young+sub-adults Adults Populationmentioning
confidence: 67%
“…Fonseca and Kierulff (1989) and Pereira et al (1993) observed the same reproductive pattern, which could be related not only to food but also to habitat availability. The habitat of this rodent in the study area was reduced due to the flooding of marshes and streams, and due to the scarcity of litter and midstore during the rainy periods (Gentile and Fernandez, 1999).…”
Section: Young+sub-adults Adults Populationmentioning
confidence: 67%
“…Sendo mais abundante entre os meses de janeiro e agosto (fim da estação chuvosa e início da estação seca) e diminuindo durante os outros meses (TALAMONI; DIAS, 1999). Em florestas semidecíduas, A. montensis pode apresentar reprodução contínua e alta taxa de sobrevivência durante os meses de maior oferta de alimento, apesar de apresentar reprodução mais intensa na estação chuvosa (CERQUEIRA et al, 1993;PEREIRA et al, 1993).…”
Section: Biologia Das Espécies De Pequenos Mamíferos Da Bacia Do Rio unclassified
“…Tais atividades podem ser classificadas como estruturadas e não estruturadas. Segundo Moreira e Gonçalves [1], enquanto na modalidade do laboratório não estruturado simplesmente se especifica o objetivo e o procedimentoé deixado a cargo do aluno, no laboratório estruturado o aluno recebe instruções que o guiam através de procedimentos destinados a produzir certos resultados específicos. Destacamos que em cada modalidade podem ser adotadas diversas abordagens.…”
Section: Introductionunclassified